Ca2+-dependent modulation of voltage-gated myocyte sodium channels. (1st November 2021) - Salvage, Samantha C.; Habib, Zaki F.; Matthews, Hugh R.; Jackson, Antony P.; Huang, Christopher L.-H.
Abstract : Voltage-dependent Na + channel activation underlies action potential generation fundamental to cellular excitability. In skeletal and cardiac muscle this triggers contraction via ryanodine-receptor (RyR)-mediated sarcoplasmic reticular (SR) Ca 2+ release. We here review potential feedback actions of intracellular [Ca 2+ ] ([Ca 2+ ]i ) on Na + channel activity, surveying their structural, genetic and cellular and functional implications, translating these to their possible clinical importance. In addition to phosphorylation sites, both Nav1.4 and Nav1.5 possess potentially regulatory binding sites for Ca 2+ and/or the Ca 2+- sensor calmodulin in their inactivating III–IV linker and C-terminal domains (CTD), where mutations are associated with a range of skeletal and cardiac muscle diseases. We summarize in vitro cell-attached patch clamp studies reporting correspondingly diverse, direct and indirect, Ca 2+ effects upon maximal Nav1.4 and Nav1.5 currents ( I max ) and their half-maximal voltages ( V 1/2 ) characterizing channel gating, in cellular expression systems and isolated myocytes. Interventions increasing cytoplasmic [Ca 2+ ]i down-regulated I max leaving V 1/2 constant in native loose patch clamped, wild-type murine skeletal and cardiac myocytes. They correspondingly reduced action potential upstroke rates and conduction velocities, causing pro-arrhythmic effects in intact perfused hearts. Genetically modified murine RyR2 -P2328S hearts modelling catecholaminergic polymorphic ventricular tachycardia (CPVT), recapitulated clinical ventricular and atrial pro-arrhythmic phenotypes following catecholaminergic challenge. These accompanied reductions in action potential conduction velocities. The latter were reversed by flecainide at RyR-blocking concentrations specifically in RyR2 -P2328S as opposed to wild-type hearts, suggesting a basis for its recent therapeutic application in CPVT. We finally explore the relevance of these mechanisms in further genetic paradigms for commoner metabolic and structural cardiac disease.